The Effect of Work Stress, Workload, and Work Motivation of Employees of the Investment Banking Division of PT. XYZ During the Implementation of Work From Home on Turnover Intention - Nicodemus Filipi Apthioman; Rudy Pramono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of work stress, workload, and work motivation of employees of the investment banking division of PT XYZ during the implementation of work from home on turnover intention. This research was conducted in Jakarta involving 48 employees of the investment banking division of PT. XYZ. Data collection was carried out by distributing a questionnaire containing 41 questions by providing alternative answers with a scale such as 1 – 5, while the questionnaire was distributed via Google from. The data obtained were then analyzed using the PLS-based SEM method. The results of this study state that work from home has a positive and significant effect on work stress, work from home has a positive and significant effect on workload, work from home has a positive and significant effect on work motivation, work stress has a positive and significant effect on turnover intention, workload positive and significant effect on turnover intention and work motivation has a negative and significant effect on turnover intention. For this reason, the management of PT XYZ should pay attention to the level of effectiveness of the application of the form of homework by paying attention to the level of work stress and the workload given. In addition, it provides motivation to employees, so as to minimize the level of turnover intention. For further research, it is expected to add other variables that are thought to affect the intention to move.